Evaluating Resident Training in Oculoplastic Surgery: A Case Series of 104 Eviscerations - Simmons, Brittany A.; Artymowicz, Anna; Gonzalez, Mithra O. (Journal of Academic Ophthalmology, 2018)
Purpose The aim of this study is to evaluate resident surgical performance based on complications after ocular evisceration.Methods A retrospective chart review of eviscerations performed between October 2011 and May 2017 by ophthalmology residents as the primary or assistant surgeon under the guidance of a single oculofacial plastic surgeon (M.O.G.) was completed. Data collected included reason for evisceration, resident participation in the case and resident's month of oculoplastic training, surgical technique, subsequent complications, and duration of follow-up.Results There were no significant differences in complication rates or surgical sequelae in resident-led versus attending-led surgeries. The complication rate for all cases in total was 5.77%. A slight negative correlation existed between the resident's month of training and the presence of postoperative complications. The number of adverse events was found to be significantly correlated with the duration of patient follow-up.Discussion Ocular eviscerations performed by ophthalmology residents as primary surgeons achieve outcomes equivalent to published reports, suggesting ocular eviscerations are a safe, effective procedure wherein residents can refine surgical skills. Some surgical sequelae may be linked to particular surgeons, implying evisceration outcomes can be used to assess resident surgical performance. Fewer adverse events arose as the resident's length of oculoplastic training increased, but this finding did not reach significance. Larger studies are needed to explore these trends.
Keywords: anophthalmic surgery; ocular evisceration; ophthalmology resident performance; oculoplastic training; ophthalmology resident outcomes